2021
DOI: 10.1101/2021.03.24.21254027
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mapping dopaminergic projections in the human brain with resting-state fMRI

Abstract: The striatum receives dense dopaminergic projections making it a key region of the dopaminergic system. Its dysfunction has been implicated in various conditions including Parkinson′s disease and substance use disorder. However, the investigation of dopamine-specific functioning in humans is problematic as the striatum is highly interconnected and current MRI approaches are unable to differentiate between dopaminergic and other projections. Here, we demonstrate that connectopic mapping —a novel approach for ch… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
(79 reference statements)
0
2
0
Order By: Relevance
“…The nature of its impact on systems that are core to dysfunction in the context of psychiatric disorders explains limited disorder-specificity, while also underscoring the relevance of investigating functions over classifications. With regards to the underlying biology, we observed brain-behavioral interactions in the dominant functional gradient, where earlier work found interactions to behavior in higher-level gradients (22, 39). This indicates the complexity of the functional organization of the striatum, but also the necessity of investigating spatially overlapping patterns of connectivity in order to fully understand striatal involvement.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The nature of its impact on systems that are core to dysfunction in the context of psychiatric disorders explains limited disorder-specificity, while also underscoring the relevance of investigating functions over classifications. With regards to the underlying biology, we observed brain-behavioral interactions in the dominant functional gradient, where earlier work found interactions to behavior in higher-level gradients (22, 39). This indicates the complexity of the functional organization of the striatum, but also the necessity of investigating spatially overlapping patterns of connectivity in order to fully understand striatal involvement.…”
Section: Discussionmentioning
confidence: 84%
“…The latter is important because in striatum we have shown that the dominant mode of connectivity change distinguishes between caudate nucleus, nucleus accumbens and putamen, while the second mode follows a rostral-caudal gradient across the three striatal substructures (21). We have also shown that topographic connectivity in the striatum is related to complex goal-directed behaviors at the individual level (21), and shows a strong correspondence with the spatial distribution of dopaminergic projections, demonstrating their potential for investigating striatal function (22). Because connectopic maps characterize complex regions such as the striatum in a way that links to behavior, we hypothesize that individual differences in connectopic maps are predictive of psychiatric symptomatology across disorders.…”
Section: Introductionmentioning
confidence: 91%